Sosialisasi Pendaftaran Merek sebagai Upaya Memberikan Kepastian dan Perlindungan Hukum bagi UMKM Agrowisata KISUCI di Desa Cipambuan, Kabupaten Bogor - Herman, KMS; Nurmawati, Bernadete; Suhendar, Tubagus Ahmad; Mandala, Subianta (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The objective of this community service project is to educate the participants of KISUCI Agrotourism MSMEs on the importance of registering their brands to provide peace of mind for consumers and ensure legal protection for their products. Cipambuan Village, Babakan Madang Sub-district, Bogor Regency, Indonesia, conducted a socialization and group discussion approach on November 4, 2024, with extension as the main activity. In the counseling session, participants were provided with a comprehensive understanding of the strategic benefits of trademarks, registration procedures through the Directorate General of Intellectual Property (DJKI), and the urgency of legal aspects in supporting business sustainability and competitiveness. In addition, the exercise uncovered a number of constraints faced by MSMEs, including a lack of technical knowledge, financial limitations, lack of awareness of the importance of legal considerations in brand registration, and an absence of familiarity with the registration process. The outreach successfully raised participants' initial awareness of the importance of brand protection, and laid the groundwork for ongoing assistance in the brand registration process as well as the development of a brand identity rooted in community strength.